Dynamic Diffusion Tensor Imaging Reveals Structural Changes in the Bilateral Pyramidal Tracts after Brain Stem Hemorrhage in Rats - Zhang, Ru-Zhi; Tao, Chuan-Yuan; Chen, Wei; Wang, Chun-Hua; Hu, Yue; Song, Li; Zhang, Bing; Chen, Yu-Shu; Xu, Zi-Qian; Wang, Lei; Feng, Hua; Wang, Ting-Hua; et al. (Frontiers in Neuroanatomy, 2016)
Background and Purpose: Few studies have concentrated on pyramidal tract (PY) changes after brain stem hemorrhage (BSH). In this study, we used a diffusion tensor imaging (DTI) technique and histologic identification to investigate longitudinal PY changes on both the contralateral and ipsilateral sides after experimental BSH. Methods: BSH was induced in 61 Sprague-Dawley rats by infusing 30 μl of autogenous tail blood into each rat’s right pons. DTI and motor function examinations were performed repeatedly on days 1, 3, 7, 14, and 28 after surgery. Fractional anisotropy, mean diffusivity, axial diffusivity, and radial diffusivity were measured in the bilateral PYs. The axon and myelin injury in the PY were evaluated by histologic study. Results: As compared with normal controls, the bilateral PYs in rats with induced BSH showed an early decrease and a late increase in fractional anisotropy and an early increase and a late decrease in mean diffusivity. A progressive decrease in axial diffusivity with dramatic axon loss from day 1 to day 28 after BSH was found bilaterally. The bilateral PYs showed an early increase and a late decrease in radial diffusivity. Early myelin injury and late repair were also detected pathologically in the bilateral PYs of rats with BSH. Thus, the early motor function deficits of rats with BSH began to improve on day 14 and had almost completely disappeared by day 28. Conclusions: DTI revealed dynamic changes in the bilateral PYs after BSH, which was confirmed by histologic findings and which correlated with motor function alteration. These findings support the idea that quantitative DTI can track structural changes in the bilateral PYs and that DTI may serve as a noninvasive tool to predict the prognoses of patients with BSH.